A journey for your beautiful mind: Economic graduate study and research - Ching-to Albert Ma (University of Oslo, Department of Economics, 2007)
A lecture to graduate students of the joint Economics Ph.D. program of the Department of Economics, University of Bergen, and the Norwegian School of Economics.
Keywords: A10; 330; Economics graduate study; economics research; Wirtschaftsstudium; Studierende; Wissenschaftliches Arbeiten; Norwegen